A detailed look into hydrogen electrochemical oxidation on ceria anodes. (1st September 2018) - Tabish, A.N.; Patel, H.C.; Schoonman, J.; Aravind, P.V.
Abstract: Using the Nernst-Planck-Poisson model and a detailed reaction mechanism, we studied the hydrogen electrochemical oxidation on a ceria anode. Resistances caused by surface kinetics, and bulk transport of oxide-ion vacancies and electrons are computed individually to identify the dominant resistive process. The effect of operating conditions like temperature and gas-phase composition on the polarization resistance is evaluated and compared with the experimental data obtained by Electrochemical Impedance Spectroscopy (EIS). The rate-determining step is found to be the charge-transfer reaction in which hydrogen adsorbs at the surface oxide ions and forms hydroxyls along with the charge-transfer to adjacent cerium ions. Based on the rate-determining step, the exchange-current density is also calculated and validated with the experimental data.